High‐Nuclear Organometallic Copper(I)–Alkynide Clusters: Thermochromic Near‐Infrared Luminescence and Solution Stability. Issue 49 (12th October 2016) - Zhuo, Hong‐Yan; Su, Hai‐Feng; Cao, Zhao‐Zhen; Liu, Wei; Wang, Shu‐Ao; Feng, Lei; Zhuang, Gui‐Lin; Lin, Shui‐Chao; Kurmoo, Mohamedally; Tung, Chen‐Ho; Sun, Di; Zheng, Lan‐Sun
Abstract: Cu(CF3 COO)2 reacts with tert ‐butylacetylene ( t BuC≡CH) in methanol in the presence of metallic copper powder to give two air‐stable clusters, [Cu I 15 ( t BuC≡C)10 (CF3 COO)5 ]⋅ t BuC≡CH (1 ) and [Cu I 16 ( t BuC≡C)12 (CF3 COO)4 (CH3 OH)2 ] (2 ). The assembly process involves in situ comproportionation reaction between Cu 2+ and Cu 0 and the formation of two different clusters is controlled by reactants concentration. The clusters consist of Cu15 and Cu16 cores co‐stabilized by strong by σ‐ and π‐bonded tert ‐butylethynide and CF3 COO − (together with methanol molecule in2 ). Their stabilities in solution were confirmed using electrospray ionization mass spectrometry in which the cluster core remains intact for1 in chloroform and acetone, and for2 in acetonitrile. Strong thermochromic luminescence in the near infrared (NIR) region was observed in the solid‐state. Of particular interest, the emission maximum of1 is red‐shifted from 710 nm at 298 K to 793 nm at 93 K, along with a 17‐fold fluorescence enhancement. In contrast, 2 exhibits red shift from 298 to 123 K followed by blue shift from 123 to 93 K. The emission wavelength was correlated with the structural parameters using variable‐temperature X‐ray single‐crystal analyses. The rich cuprophilic interaction plays a significant role in the formation of 3 LMCT ( t BuC≡C→Cux ) excited state mixed with cluster‐centered ( 3 CC) characters, which can be considerably influenced by temperature, leading to thermochromic luminescence. The present work provides 1) a new synthetic protocol for the high‐nuclear Cu I –alkynyl clusters; 2) a comprehensive insight into the mechanism of thermochromic luminescence; 3) unusual emissive materials with the characters of NIR and thermochromic luminescence simultaneously. Abstract : Unusual behavior : Two copper(I)‐alkynyl clusters were synthesized by in situ comproportionation reaction and show unusual thermochromic luminescence in the near infrared (NIR) region. The correlations between structure and thermochromic luminescence behavior were further elucidated by variable‐temperature X‐ray single‐crystal analyses (see figure).